Modernizacja przestrzeni i co dalej? = Modernizing Space - What's Next? - Cioch-Ciućmańska, Marzena (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The Public Library in Szprotawa has been shaping its services for nearly 80 years. This article focuses on the institution's recent years, during which initiatives have been undertaken to ensure the continuous development of reading and a diverse range of cultural activities. In 2023, the Municipal Public Library in Szprotawa established the multimedia Orange Lab, and the Children's Section was renovated. In 2024, the institution received funding for the project "Modernization of the Municipal Public Library Building in Szprotawa" under Intervention Direction 2.1 "Library Infrastructure 2021-2025," Priority 2 of the National Reading Development Program 2.0. The project is valued at 3 million PLN, with a granted subsidy of 2.25 million PLN. Future plans include further modernization?an application has been submitted under the European Funds for Lubuskie Program 2021-2027, Priority 2 "European Funds for Green Development in Lubuskie," Action 2.1 "Energy Efficiency ? Grants" and for the construction of an elevator with support from the Regional Social Policy Centre.These projects are successfully implemented thanks to inter-institutional collaboration, the dedication, and creativity of librarians. Daily work and local community engagement result in satisfying statistical indicators.
Keywords: biblioteka; Szprotawa; współpraca; fundacja; Dyskusyjny Klub Książki; Pracownia Orange; Narodowy Program Rozwoju Czytelnictwa; fundusze europejskie; modernizacja; edukacja; library; collaboration; foundation; Book Discussion Club; Orange Lab; Library Development Program; National Reading Development Program; European funds; education; modernisation